Monitoring the psychological and physiological effects of 320k Sochi-Giresun marathon elite open water master swimming event - KARAGÖZOĞLU, CENGİZ (My University, 2023)
This study aims to investigate the psychophysiological responses of master swimmers from beginning to end of the Sochi-Giresun 320 km open water swimming event. Candidate swimmers were evaluated according to several criteria which are national and international competition experience, the ability to swim an average of 1 km in hour, experience in night swimming, and sports background. Selected from a total of 48 candidates from Turkey, Russia, and Germany, the group of 15 athletes comprises a balanced gender distribution, with 9 males and 3 females. Additionally, 3 reserve athletes were also identified. Participants were subjected of various assessments, including a personal information form, blood lactate sample, VAS scales and IZOF measurements. The research procedure involved VAS, IZOF and blood lactate measurements before swimming, transferring to the water according to their swimming order, commencing swimming upon the referee’s command, recording time and distance with GPS location, transferring to the ship after swimming round, collecting after swim VAS, IZOF, and blood lactate samples. Research findings revealed some psychological differences between nighttime and daytime open-water swimming results. Male swimmers exhibited higher levels of perceived stress level and perceived difficulty level. Factors negatively affecting performance included post-swim blood lactate levels, perceived fatigue, the difficulty of the swimming round, and perceived stress levels. These results indicate that athletes’ psychological states can vary individually and have complex effects on performance. The lower levels of stress and fatigue among athletes might be related with their participation in national and international competitions, relatively higher average age, and consequently elevated levels of performance and psychological maturity.

Bu çalışanın amacı Soçi-Giresun 320 km açık su yüzme etkinliğinde başlangıçtan bitişe kadar master yüzücülerinin psiko-fizyolojik tepkilerini incelemektir. Aday yüzücüler, ulusal ve uluslararası yarış deneyimi, ortalama 1 km’yi bir saatte yüzebilme yeteneği, gece yüzme deneyimi, spor geçmişine sahip olmak gibi kriterlere göre değerlendirildi. Türkiye, Rusya ve Almanya’dan 9’u erkek ve 3’ü kadın olmak üzere 15 sporcu yer almaktadır. Ayrıca, bu gruba ek olarak 3 yedek sporcu da belirlenmiştir. Katılımcılara kişisel bilgi formu, laktat ölçümleri, VAS ölçekleri ve IZOF ölçümleri uygulandı. Araştırma prosedürü, teknede VAS ve kan laktat örneklerinin alınması, yüzme sırasına göre transfer botuyla suya taşıma, hakemin komutuyla yüzmeye başlama, zaman ve mesafe için GPS konumu kaydetme, yüzme turunun bitiminde tekrar gemiye transfer ve yüzme sonrası VAS, İZOF ve laktat ölçümlerinin alınmasını içermiştir. Araştırma sonuçları, gece ve gündüz yüzme sonuçları arasında psikolojik faktörler açısından bazı farklılıklar olduğunu göstermiştir. Erkek yüzücülerde daha yüksek düzeyde algılanan stres seviyesi ve algılanan zorluk derecesi belirlendi. Bu sonuçlar, sporcuların psikolojik durumlarının bireysel olarak değişebileceğini ve performans üzerinde karmaşık etkilere sahip olabileceğini göstermektedir. Sporcuların stres ve yorgunluk seviyelerinin düşük çıkmasının nedeni, ulusal ve uluslararası düzeyde katıldıkları yarış deneyimleri, yaş ortalamalarının yüksek olması ve bu iki kritere olarak yüksek performansa ve psikolojik olgunluğa sahip olmaları ile açıklanmaktadır.
20 km Sochi-Giresun açıksu elit master yüzme maraton etkinliğinin psikolojik ve fizyolojik etkilerinin incelenmesi
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Diğer; Eğitim; Spor Bilimleri ve Teknolojisi; Social Sciences and Humanities; Psychology; Other; Education; Sports Sciences and Technology; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Psikoloji (çeşitli); Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); General Psychology; Social Sciences & Humanities; Aerobik kapasite; yüzme; master yüzücü; açıksu; marathon